THE EFFECT OF INFORMATION TECHNOLOGY CAPABILITY, AND STRATEGIC PLANNING ON KNOWLEDGE MANAGEMENT MEDITED ORGANIZATIONAL PERFORMANCE IN THE ARMY CENTRAL IMPLEMENTING AGENCY - Daryanto, Eko; Jasfar, Farida; Kusnadi (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this study is to provide input to the leadership of the Indonesian Army National Armed Forces Headquarters regarding the importance of knowledge management on technological developments because this knowledge is one way to create and improve work professionalism in the military, especially the Indonesian Armed Forces.The research design and method used in this research is hypothesis testing. This research is a quantitative non-experimental, using a questionnaire given to 93 respondents. This research was conducted at the Central Implementing Agency for the Indonesian National Armed Forces.The results of this study indicate that: The effect of Information Technology Capability, Strategic Planning on Organizational Performance is positive and significant. The influence of Knowledge Management on Organizational Performance is positive and significant. The influence of Knowledge Management mediating Information Technology Capability, Strategic Planning on Organizational Performance is positive and significant. It means that the higher/positive mediation of Knowledge Management on Information Technology Capability, Strategic Planning, the higher/positive Organizational Performance.Theoretical implications: Knowledge Management as a mediating of Information Technology Capability, Strategic Planning is able to improve Organizational Performance, by increasing Knowledge Management through increasing its dimensions it will be able to improve the Organizational Performance of the Central Implementing Body of the Indonesian Armed Forces.